2021
DOI: 10.1371/journal.pone.0260864
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SFRP2 facilitates cancer stemness and radioresistance of glioma cells via activating Wnt/β-catenin signaling

Abstract: Secreted frizzled-related protein 2 (SFRP2) is a glycoprotein with frizzled-like cysteine-rich domain that binds with Wnt ligands or frizzled receptors to regulate Wnt signaling. SFRP2 is frequently hypermethylated in glioma patients, and analysis of TCGA data indicates that SFRP2 is one of the most downregulated genes in radiotherapy treated glioma patients. In the present study, we aimed to explore the potential function of SFRP2 in tumorigenesis and radioresistance of glioma. The RNA sequencing data of TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We analyzed TOP2A expression in different molecular subtypes of MB based on GEO datasets, and the results revealed that the expression of TOP2A was significantly higher in the WNT and non-WNT/non-SHH groups than in the SHH group. Previous studies have reported that activation of the Wnt/ b-catenin signaling pathway contributes to radioresistance in most tumor types, including glioma, hepatocellular carcinoma, and nasopharyngeal carcinoma (49)(50)(51). However, radiation resistance among the different molecular subtypes of MB has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed TOP2A expression in different molecular subtypes of MB based on GEO datasets, and the results revealed that the expression of TOP2A was significantly higher in the WNT and non-WNT/non-SHH groups than in the SHH group. Previous studies have reported that activation of the Wnt/ b-catenin signaling pathway contributes to radioresistance in most tumor types, including glioma, hepatocellular carcinoma, and nasopharyngeal carcinoma (49)(50)(51). However, radiation resistance among the different molecular subtypes of MB has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…rough the activation of Wnt/-catenin signaling, the CRISP/Cas9-mediated reduction of SFRP2 facilitated the development of soft agar colonies, cancer stemness, and radioresistance in glioma cells [33]. Zhang et al reported that when compared to the paired adjacent nontumor tissue, the amount of SFRP2 mRNA in NSCLC tissue was found to be significantly lower, while the amount of SFRP2 gene methylation was found to be significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…A study con rmed for the rst time the role of SFRP2 in the radiation resistance of glioma cells and SFRP2 is one of the most downregulated genes in radiotherapy treated glioma patients. (24). Li et al indicated that Notch1 can promote invasion, selfrenewal and growth of glioma-initiating cells and is overexpressed in glioma-initiating cells (25).Lan et al con rmed WNT7A is upregulated as a tumor promoter in glioma (26).…”
Section: Discussionmentioning
confidence: 99%